Analysis and forecast of the HIV/AIDS epidemic in Mainland China, 1985–2016. (28th October 2019) - Guo, Zuiyuan; Xiao, Dan; Xu, Shuang; He, Kevin
Abstract: Background: We aimed to forecast the number of unidentified and newly acquired HIV-infected individuals each year and to estimate the effectiveness of government prevention and control programs in China. Methods: Dynamic and stochastic models were established based on officially published data regarding the four main modes of transmission: male homosexual sexual behavior, heterosexual sexual behavior, injection drug use (IDU) and plasma donation. Finally, we performed sensitivity analyses on model parameters. Results: Nationally, by December 2016, approximately 280 790 individuals were estimated to have an unidentified HIV infection, with transmission via male homosexual sexual behavior ( n  = 100 710), heterosexual sexual behavior ( n  = 174 310), IDU ( n  = 5 620) and plasma donation ( n  = 150). Moreover, 196 970 newly acquired HIV-infected individuals were expected in 2016, via male homosexual sexual behavior ( n  = 78 610), heterosexual sexual behavior ( n  = 116, 540), IDU ( n  = 1820), and plasma donation ( n  < 2). Conclusions: Our results show that HIV transmission via IDU and plasma donation has been effectively controlled; transmission via heterosexual sexual contact is being somewhat controlled; however, transmission via male homosexual sexual contact is not controlled. Hence, China should strengthen efforts aimed at control of unsafe sexual behaviors.